Pursuing Trayvon Martin: Historical Contexts and Contemporary Manifestations of Racial Dynamics - Yancy, George; Jones, Janine (Lexington Books, 2012)
On February 26, 2012, seventeen-year-old African American male Trayvon Martin was shot and killed by George Zimmerman, a twenty-eight-year-old white Hispanic American male in Sanford, Florida. Zimmerman killed Martin in a gated community. Pursuing Trayvon Martin: Historical Contexts and Contemporary Manifestations of Racial Dynamics, featuring a new preface by editors George Yancy and Janine Jones written after the June 2013 trial, examines the societal conditions that fueled the shooting and its ramifications for race relations and violence in America. Pursuing Trayvon Martin: Historical Contexts and Contemporary Manifestations of Racial Dynamics attempts to capture what a critical cadre of scholars think about this potentially volatile situation in the moment. The text addresses issues across various thematic domains that are both broad and relevant. Pursuing Trayvon Martin is an important read for scholars in the fields of philosophy, criminal justice, history, critical race theory, political science, critical philosophies of race, gender studies, sociology, rhetorical studies, and for anyone hungry for critical ways of thinking about the Trayvon Martin case.